LOW BIRTH WEIGHT AS A KEY DETERMINANT OF CHILDHOOD STUNTING: A MATERNAL–NEONATALRISK FACTORS ANALYSIS INA STUNTING LOCUS AREA - Nindi Pramesthi; Renidya Asyura Muttabi' Deya Fa'ni; Rochmanita Sandya Afindaningrum; Honesty Pujiyani; Nadia Dian Rosanti (Universitas Kusuma Husada Surakarta, 2026)
Background: Many studies have examined the effects of inadequate nutritional intake, showing an increased risk of infectious diseases, death, and obstacles to children's growth and development. According to the results of SSGI 2024, the prevalence of stunting among children under five was 19.8%; this figure remains far from the medium-term national target. This research aims to determine the determinants of stunting in a stunting-affected area.Methods: A quantitative analytical study with a case-control approach was used in this study. The research was conducted in Buker Village, one of the stunting loci in Sampang Regency. The research subjects consisted of 35 stunted toddlers in the case group and 40 toddlers with normal nutritional status in the control group. Data analysis in this study included univariate analysis using frequency distributions, bivariate analysis using the chi-square test, and multivariate analysis using multiple logistic regression.Results: The results showed that the most dominant factor associated with stunting was a history of low birth weight (LBW) OR 24,1 (95% CI: 2,573 – 226,647), which means that toddlers who were born with LBW had a 24,1 times higher chance of stunting.Conclusion: This study identifies low birth weight as a key determinant of stunting, as affected infants face developmental vulnerabilities. Strengthening maternal nutrition, infection prevention, and postnatal growth monitoring is essential to mitigate long-term growth deficits. These findings emphasize the importance of integrating maternal nutrition programs with neonatal monitoring, particularly in high-burden settings, to effectively improve child growth outcomes.